Development of Canva-Based Interactive Learning Media with PBL Approach for Fourth Grade IPAS Lessons - Putri, Hafifa; Yeni Erita (Journal of Practice Learning and Educational Development, 2025)
Education plays a crucial role in the development of the Society 5.0 era, which encourages the renewal and utilization of technology to facilitate learning through digital-based media. However, in reality, conventional media are still widely used, and many teachers are not yet able to optimize technology to innovate learning media. This study aims to produce a valid and practical interactive learning media using the Canva application for IPAS learning based on Problem-Based Learning (PBL) in fourth grade of elementary school. This is a research and development study applying the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The research was conducted in Cluster 5 of Lembah Gumanti District, involving three elementary schools: SDN 02 Sungai Nanam, SDN 18 Sungai Nanam, and SDN 26 Sungai Nanam. The developed media were validated by experts and tested in the aforementioned schools to measure practicality. The results showed that the developed media achieved a validation score of 97%, categorized as very valid. Practicality results based on teacher responses reached 95.23%, and student responses reached 97.57%, both categorized as very practical. Therefore, the developed Canva-based interactive learning media for PBL-oriented IPAS learning is proven to be highly valid and practical